Long distance communication using localized optical soliton via entangled photon - Amiri, I. S. (International Organization of Scientific Research, 2013)
A system of microring resonators (MRRs) is presented to generation entangled photon. Different time slot for continuous variable quantum key distribution (CVQKD) use is applicable in optical wireless link. Chaotic behavior of a soliton pulse within the device can be presented respect to the Kerr nonlinear type of light in the MRR devices. Continuous spatial and temporal signals are generated spreading over the spectrum. The CVQKD is formed using the localized spatial soliton pulse. Here localized temporal soliton with FWHM and FSR of 0.2 ps and 0.58 ns is obtained respectively. The spatial soliton pulse has a FWHM of 80 pm. Transmission of soliton pulse with FWHM of 1.5 ps is simulated along the long distance fiber optics where the polarized photons are formed incorporating with the polarization control unit into the MRRs, which allows different time slot entangled photons to be randomly formed.